STUDI KOMPARATIF : KINERJA KEUANGAN PEMERINTAH DAERAH SARBAGITA DENGAN KINERJA KEUANGAN PEMERINTAH PROVINSI BALI - Adnyani, Ni Putu Novianti Wira; Wiagustini, Ni Luh Putu (E-Jurnal Manajemen; Vol 7 No 2 (2018)DO - 10.24843/EJMUNUD.2018.v7.i02.p20, 2018)
The implementation of the regional autonomy system requires local government officials to be able to manage finances in their regions effectively and efficiently. The purpose of this research is to explain the comparison and significance of the difference between the financial performance of Denpasar city government, Badung regency, Gianyar and Tabanan districts with the financial performance of Bali provincial government during 2011-2015 in terms of regional financial independence, DDF, PAD effectiveness, growth of PAD, the compatibility of spending and expenditure efficiency. The result of this research is the financial performance of Denpasar city government is superior compared to the financial performance of Bali provincial government from the effectiveness of PAD, the growth of PAD and the harmony of expenditure. The financial performance of the local government of Badung district is superior compared to the Balinese provincial government's financial performance of all ratios except the expenditure efficiency ratio. The financial performance of the Gianyar district government is superior to the financial performance of the provincial government of Bali in terms of PAD effectiveness, PAD growth and harmonized spending. The financial performance of Tabanan district government is superior compared to Bali province in terms of PAD effectiveness and PAD growth. K eywords: regional financial performance